Dump More, Worry Less: Euphoric Nescience in Recompense Through Waste Trading - Zhou, Nancy (Tufts Archival Research Center, 2022)
An in-depth investigation of the international waste trade by examining the scale of such transboundary trash movements through the World Trade Organization, and the causes and consequences of China’s 2017 foreign waste ban with the corresponding General Agreement on Tariffs and Trade (GATT) treaties, such as Article XI on the general elimination of quantitative restrictions and Article XX on general exceptions of international trade. An exploration of economic and environmental factors, including regional income level and domestic waste generation, in comparative advantage and sovereign risk assessment, is followed by a discussion of the realities of local waste dumping and the domestic capacity for waste treatment (incinerate, recycling, and landfilling). Research aims to present a prescription for both domestic waste management policies and international law to determine the legitimacy of the legal parameters of foreign waste import prohibition while identifying general lessons for international environmental policy that emerge from the transactions of garbage.; Thesis (B.A.)--Tufts University, 2022.; Submitted to the Program of International Relations.; Keywords: International Waste Trade, GATT 1994, WTO, Environmental Kuznets Curve, Resource Distribution, Globalization.